2016
DOI: 10.1074/jbc.m116.724856
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Roles of Elongation Factor-2 Kinase in Stem Cell Survival

Abstract: Protein synthesis inhibition is an immediate response during stress to switch the composition of protein pool in order to adapt to the new environment. It was reported that this response could be either protective or deleterious. However, how cells choose to live or die upon protein synthesis inhibition is largely unknown. Previously, we have shown that elongation factor-2 kinase (eEF2K), a protein kinase that suppresses protein synthesis during elongation phase, is a positive regulator of apoptosis both in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…9c ). In addition, we chose the Eef2k gene as a tandem GATA motif-containing gene from the ENCODE dataset since Eef2k is known to regulate HSC apoptosis 44 and found changes in expression in G2 R398W/+ mice (Fig. 9d ).…”
Section: Resultsmentioning
confidence: 99%
“…9c ). In addition, we chose the Eef2k gene as a tandem GATA motif-containing gene from the ENCODE dataset since Eef2k is known to regulate HSC apoptosis 44 and found changes in expression in G2 R398W/+ mice (Fig. 9d ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, others have also reported that maintaining the equilibrium of the Akt-mTOR signaling pathway is critical for promoting T cell quiescence, longevity, and homeostasis (32). In addition, elevations of HSP90 and the phospho-Akt proteins have been reported in other types of cells deficient in eEF-2K, including the intestinal stem cells, epithelial cells (33), human tumor cells, and mouse embryonic fibroblasts (21). Similarly, we found that the up-regulations of this signaling also occur in CD8 + T cells subjected to eEF-2K ablation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, eEF2K shows opposing functions in stem cells. One study showed that eEF2K knock-out mice were protected from hematopoietic syndrome yet hypersensitive to gastrointestinal syndrome ( Liao et al, 2016 ). eEF2K also functions to maintain germline quality via regulating apoptosis by controlling translation of the anti-apoptotic proteins XIAP and c-FLIPL in oocytes from C. elegans ( Chu et al, 2014 ).…”
Section: Additional Pathologies Involved In Eef2k Regulationmentioning
confidence: 99%